MINIMIZING AGENCY PROBLEMS IN MUDHARABAH CONTRACTS THROUGH THE PRINCIPLE OF TAUHID - Irfan Ramis; Hardianti Nur; Muhammad Wahyuddin Abdullah; Rusmadi Rijal Saleh (Universitas Islam Darul 'ulum Lamongan, 2025)
This research aims to minimize the agency problem in mudharabah contract through tawhid principle. This research works with qualitative approach which applies the method of library research by implementing the literature review. Agency theory focuses on two aspects, the principal and the agent where the principal as the owner (shahibul maal) and the agent as the manager (mudharib). Agency problem takes place after the work, there are three conflicts during the agency problem; purpose conflict, behavior conflict, and asymmetric information conflict. Mudharabah is the corporation system which has declared position in Islam. Mudharabah is basically a contract of profit and loss sharing in which one side trusts some capitals to an investor. As the result, he will get what has been determined from the profit/loss of the business invested. This kind of contract requires transparency of the businessman. If one of the main sides especially mudharib does not report everything transparently, there will be activities called adverse selection and moral hazard. The mudharabah contract is a finance contract full of asymmetric information. The effort of minimizing the agency problem is inserting the Tawhid principle where Allah is the truest witness of all contracts. Based on the Tawhid principle and ethics considering the purpose or maqashid al-syariah; Keeping religion (Faith), keeping the wealth, keeping mind, keeping souls and children. The tawhid values must be implemented in our daily muamalah such as honesty, ransparency, trusty, and well-believed in economic activity.